Community Perspectives on the Creation of a Hospital-Based Doula Program (Mary Ann Liebert, 2021)
Objective: Racial and ethnic inequities in perinatal health outcomes are pervasive. Doula support is an evidence-based practice for improving maternal outcomes. However, women in lower-income populations often do not have access to doulas. This study explored community perspectives on doula care to inform the development of a hospital-based doula program to serve primarily low-income women of color. Methods: Four focus groups and four individual interviews were conducted with: (1) women who were pregnant or parenting a child under age 2 (n=20); (2) people who had provided support during a birth in the previous 2 years (n=5); and (3) women who had received doula training (n=4). Results: Participants had generally positive perceptions of doula services. Many aspects of doula support desired by participants are core to birth doula services. Participants identified ways that doulas could potentially address critical gaps in health care services known to impact outcomes (e.g., continuity of care and advocacy), and provide much-needed support in the postpartum period. Responses also suggested that doula training and hospital-based doula programs may need to be adapted to address population-specific needs (e.g., women with substance use disorder and younger mothers). Novel program suggestions included ?on call? informational doulas. Conclusions: Findings suggested that women in racial/ethnic minority and lower income groups may be likely to utilize a hospital-based doula program and identified adaptations to traditional doula care that may be required to best meet the needs of women in groups with higher risk of poor maternal health and birth outcomes.